2021
DOI: 10.3389/fmicb.2021.627327
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Characterization of the Microbiome and Virome of Questing Ticks

Abstract: Due to their vector capacity, ticks are ectoparasites of medical and veterinary significance. Modern sequencing tools have facilitated tick-associated microbiota studies, but these have largely focused on bacterial pathogens and symbionts. By combining 16S rRNA gene sequencing with total RNA-sequencing methods, we aimed to determine the complete microbiome and virome of questing, female Ixodes holocyclus recovered from coastal, north-eastern New South Wales (NSW), Australia. We present, for the first time, a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…The complete or partial genomes of 12 viruses were identified in tick samples (Table 2). The virome of I. holocyclus has been interrogated previously (Chandra et al, 2021;Harvey et al, 2019;O'Brien et al, 2018), and seven of the eight viruses identified are 6).…”
Section: Tick-associated Virusesmentioning
confidence: 99%
“…The complete or partial genomes of 12 viruses were identified in tick samples (Table 2). The virome of I. holocyclus has been interrogated previously (Chandra et al, 2021;Harvey et al, 2019;O'Brien et al, 2018), and seven of the eight viruses identified are 6).…”
Section: Tick-associated Virusesmentioning
confidence: 99%
“…However, the presence of PVL1 in the viscera and salivary glands of ticks from Queensland is particularly interesting in the context of IhIV, which was also identified in both the salivary glands and viscera of I. holocyclus ticks but did not replicate in ISE6 cells [ 34 ]. Neither the four virus-like sequences described in this study nor their relatives described in [ 20 ] were identified in a recent meta-transcriptomic study performed on unfed adult I. holocyclus ticks collected in Northern NSW [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-transcriptomic surveys of ticks from New South Wales (NSW), Australia, have identified a number of novel virus sequences including Shelly Headland virus, which groups with the human pathogens Colorado tick fever virus and Eyach virus [ 20 , 21 ]. While next generation sequencing technologies are an invaluable asset in the field of virus discovery, isolation of viruses of interest is necessary to further our understanding of host range and pathogenesis for potential emerging viruses [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of tick-borne pathogens have been reported, heartland virus 11 , tick-borne encephalitis virus 12 , Borrelia burgdorferi sensu lato 13 , Rickettsia rickettsi 14 , severe fever with thrombocytopenia syndrome virus 8 , are just a few examples of important pathogens that pose threats to human health. However, the diversity of tick-borne infectious diseases remained underestimated, since the investigations tended to be heavily biased toward research on microorganisms that infect humans or animals of economic and social importance 15 , 16 . The advent of advanced technologies such as high-throughput sequencing, meta-genomics, meta-transcriptomics, etc., had enabled a systematic understanding on a high variety of pathogenic or non-pathogenic, known or unknown, endogenous or exogenous microorganisms that are carried by ticks 9 , 15 , 16 .…”
Section: Background and Summarymentioning
confidence: 99%